Serological Evidence of Natural Exposure to Tick-Borne Pathogens in Horses, Romania - Andreea Monica Bogdan; Mariana Ionita; Ioan Liviu Mitrea (Microorganisms, 2021)
The purpose of this study was to investigate the seroprevalence of selected tick-borne-pathogens (TBPs) among Romanian horses. For this, a total of 223 animals originating from north, central, and southeast Romania, including horses from stud farms (n = 118) and working horses (n = 105), were tested using a commercial rapid ELISA-based test. Overall, 10.3% (95% confidence interval (CI): 6.7–15.1%) of the tested horses were seropositive for antibodies (Ab) against Anaplasma phagocytophilum. Additionally, 18.8% (95% CI: 13.9–24.6%) and 0.5% (95% CI: 0.01–2.5%) of horses were seropositive for Ab against Borrelia burgdorferi sensu lato and Ehrlichia spp., respectively. Among the tested horses, 3.1% were seroreactive to two or three pathogens. These findings show the natural exposure of Romanian horses to zoonotic tick-borne pathogens and emphasize the need for further studies to better understand the epidemiology of equine tick-borne diseases in Romania.